Exploring Student Learning Experiences through the Implementation of the Project-Based Learning Model at SMK Syntax Bisnis School Kuningan - Saona Saona; Dena Agustina; M. Abdurohman M. Abdurohman; Ahmad Rifai; Putri Damayanti (Publikasi Indonesia, 2025)
21st-century education demands a transformation from teacher-centered to student-centered learning that emphasizes the development of critical thinking, collaboration, and problem-solving skills. Project-Based Learning (PjBL) has emerged as an innovative approach that addresses these challenges, but an in-depth understanding of students' subjective experiences in PjBL remains limited. This study aims to explore and deeply understand students' learning experiences in implementing the Project-Based Learning Model at SMK Syntax Bisnis School Kuningan. The study used a qualitative approach with a phenomenological design, involving 14 student participants selected through purposive sampling. Data were collected through in-depth interviews, participant observation, and document analysis, then analyzed using the Colaizzi phenomenological analysis method. The results identified six main themes: the dynamics of experience at each stage of the project; facilitative factors (teacher support, authentic design, positive group dynamics); challenges faced (time management, interpersonal conflict, skill limitations); shifting perspectives on challenges; development of multidimensional competencies; and the fundamental transformation from passive to active learners. The study concluded that PjBL provides a transformative experience that develops a sense of ownership, resilience, and 21st-century competencies, with practical implications for teacher training, project design, skills scaffolding, and systemic support.